Insomnia and Quality of Life in The Elderly: WHOQOL-BREF and WHOQOL-OLD Indonesian Version (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
In Indonesia, the elderly are someone who has reached the age of 60 years old and over. Along with the aging, there will be changes in sleep pattern and awakening process so that insomnia will appear. Insomnia can cause decrease in quality of life. The aim of this study was to analyze the relationship between insomnia and quality of life in elderly which measured by WHOQOL-BREF and WHOQOL-OLD Indonesian version. The quantitative analytical cross-sectional study had been carried out to 60 elderly from 6 public health centers (puskesmas) in Bandung City, West Java, Indonesia. This study was conducted from August to November 2019. Insomnia was measured by Insomnia Severity Index and quality of life was measured by WHOQOL-BREF and WHOQOL-OLD Indonesian version. The Spearman correlation test was used for data analysis. This study discovered that the proportion of insomnia in the elderlyÂ was 36,7%(95%ci:24.5%-48.9%).the correlation coefficient between insomnia and quality of life was -0,386 (WHOQOL-BREF) and -0,302 (WHOQOL-OLD). It can be concluded that the proportion of insomnia in the elderly is high and Â there is a correlation between insomnia and quality of life even though the correlation is weak.